Representations and perceptions of anxiety about the future of artistic expression for students in middle school (Al-Academy, 2017)
The tensions and crises and the psychological pressure as well as the rapid changes and great development which is taking place in the present time. And witnessing community of wars and conflicts that give rise to future concern among members of the community in general and students in particular, as it included the current research a number of chapters, the First chapter contains the research problem, the important goal, then set researcher terminology that has defined and contained in the title of research in the form (concern the future, artistic expression, middle school). The Second chapter included three sections, the first included the nature of adolescence and traits, characteristics and problems, and included the second topic on the concept of anxiety and philosophy, its causes and types, while the third section focused on the importance of artistic expression, types and stages as a breather baptizing him the student to express what touring at the same feelings and emotions . The Third chapter, limited the research methodology and procedures. The Fourth chapter, it has emerged as the results, and in light of the results of the research and the researcher developed a number of recommendations and suggestions and finally proven sources and references.